Student engagement with self-instructional course materials : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education in Distance and On-line Learning at Massey University, Extramural, New Zealand - Cowie, Peter; Cowie, Peter (Massey University, 2010)
This study is concerned with understanding how students engage with self-instructional materials on campus and at a distance within the context of the hybrid course offered at ABC College. This study examines the interrelationship of (a) time engaged with course materials, (b) the perceived value of course materials, (c) student approaches to engagement and (d) the integration of the course materials into the student learning experience in order to construct an understanding of student engagement with course materials. This study employed multiple case studies which formed a holistic collective case study. Data on student engagement with the course materials was collected using a questionnaire instrument. The resulting data was analysed using descriptive statistics to create a picture of how students engaged with the course materials. Correlation statistics were used to identify possible relationships between the items. Emerging themes were then explored in focus groups. Subsequent analysis of the focus group data explored the causation and interrelationships between themes resulting in an understanding of student engagement with the course materials. The findings from this study suggests that student engagement with self-instructional course materials (readings, learning guide, multimedia, etc.) are the result of complex interactions between a student's preferred approach to engagement, their locus of control and the method of integration of the course materials. The majority of participants preferred to engage with the course materials using a deep approach. Participants with an external locus of control reflected the assumptions and approaches they perceived from the method of integration. Participants with an internal locus of control engaged with the course materials using their preferred approach unless they were convinced that another approach served their needs better. The majority of participants exhibited an external locus of control. When a presentation or supplemental method of integrating was used, participants were more likely to engage with the course materials using a surface approach to engagement. They were also more likely to spend less time engaging with the course materials and place a lower value on the course materials. When a discussion or springboard method of integration was used participants were more likely to engage the course materials using a deep approach to engagement. They were also more likely to spend more time engaging with the course materials and place a higher value on the course materials.
Keywords: Distance education; Independent study; Student learning